PENGARUH KUALITAS PELAYANAN DAN KINERJA KARYAWAN TERHADAP KEPUASAN PENUMPANG PADA PT. KERETA COMMUTER INDONESIA (STUDI KASUS DI STASIUN JUANDA) - Pradana, Ricki; Krishantoro, Krishantoro (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The purpose of this research is (a) to determine the effect of service quality on customer satisfaction at PT. KCI at Juanda train station.(b) determine the effect of employee performance on PT customer satisfaction. KCI at Juanda train station. (c) To determine the effect of service quality and employee performance on customer satisfaction at PT. KCI at Juanda train station. The method used is a type of quantitative research with a sample of 100 respondents filling out a questionnaire. The collected data was recorded and then analyzed using SPSS (Statistical Program for Social Science) 25.0 for Windows. The research results show that respondents' assessments are usually related to the quality of service and performance of PT employees. KCI at Juanda station is good. This means that the independent variables or service quality and employee performance on customer satisfaction together (together) are 44.8%. The remaining 55.2% is influenced by other factors.